1. Distribute the -6 to both terms inside parentheses:
-6(x + 3) = -6x - 18
2. Combine like terms on the left side of the equation:
-6x - 18 + x = -6x + 30
3. Simplify the equation:
-5x - 18 = -6x + 30
4. Add 6x to both sides of the equation:
4x - 18 = 30
5. Add 18 to both sides of the equation:
4x = 48
6. Divide both sides of the equation by 4:
x = 12
Order the the steps to solve the equation for x. Make sure to put the steps in order. Not all steps will be used.
-6(x + 3) +x = -6x + 30
x = 12
-6x -18 + 4x = -6 x + 30
-6x +3 + 4x = -6x + 30
4x - 18 = 30
-8x + 3 = 30
-2x -18 = -6x + 30
4x = 48
-8x = 27
x = -27/8
3 answers
no
Apologies for the incorrect order. Here is the correct order of steps:
1. Distribute the -6 to both terms inside parentheses:
-6(x + 3) = -6x - 18
2. Combine like terms on the left side of the equation:
-6x - 18 + x = -6x + 30
3. Simplify the equation:
-5x - 18 = -6x + 30
4. Add 6x to both sides of the equation:
-5x + 6x - 18 = -6x + 6x + 30
5. Combine like terms on both sides of the equation:
x - 18 = 30
6. Add 18 to both sides of the equation:
x - 18 + 18 = 30 + 18
7. Simplify the equation:
x = 48
Therefore, the correct solution is x = 48.
1. Distribute the -6 to both terms inside parentheses:
-6(x + 3) = -6x - 18
2. Combine like terms on the left side of the equation:
-6x - 18 + x = -6x + 30
3. Simplify the equation:
-5x - 18 = -6x + 30
4. Add 6x to both sides of the equation:
-5x + 6x - 18 = -6x + 6x + 30
5. Combine like terms on both sides of the equation:
x - 18 = 30
6. Add 18 to both sides of the equation:
x - 18 + 18 = 30 + 18
7. Simplify the equation:
x = 48
Therefore, the correct solution is x = 48.